Enhanced degradation of tetrabromobisphenol A by Fe3+/sulfite process under simulated sunlight irradiation. (December 2021) - Wang, Zongping; Cao, Lisan; Wan, Ying; Wang, Jingwen; Bai, Fan; Xie, Pengchao
Abstract: Degradation of tetrabromobisphenol A (TBBPA), an emerging micropollutant, by photo/Fe 3+ /sulfite process was investigated under different operational conditions and water matrices. 91% of TBBPA was efficiently degraded within 30 min in the Fe 3+ /sulfite system under sunlight irradiation when the initial pH was 6.0, which is much higher than that of TBBPA without irradiation (52%). The acceleration of radical generation and direct photolysis by photo irradiation were responsible for the enhanced TBBPA degradation. Although this process showed better performance on TBBPA degradation in weak acid conditions, the high removal efficiency was also achieved at near-neutral pH. HO, SO4 − and direct photolysis contributed to TBBPA degradation. Direct photolysis and SO4 − presented the dominant contribution. The degradation rate increased with elevating the Fe 3+ dose (10–40 μM), but slightly decreased when the Fe 3+ dose was further raised to 100 μM. Similarly, the degradation efficiency initially increased with increasing the sulfite dose (100–400 μM), but decreased when the sulfite concentration reached 1000 μM. Dissolved oxygen played a crucial role in TBBPA degradation, the presence of water matrices such as humic acid (0.8–4.0 mg/L), bicarbonate (0.5–10 mM) and chloride (0.5–10 mM) retarded TBBPA degradation. This study proposed a new efficient strategy to enhance TBBPA degradation in the Fe 3+ /sulfite process. Graphical abstract: Image 1 Highlights: Photo irradiation accelerated TBBPA degradation in the Fe 3+ /sulfite process. SO4 − oxidation and photolysis dominated TBBPA degradation in the system. TBBPA can be efficiently degraded in the system at near neutral pH. Effects of typical operational conditions and water matrices were evaluated.